A metal–organic framework nanocomposite with oxidation and near-infrared light cascade response for bacterial photothermal inactivation - Dorma Momo, Christopher; Zhou, Yuan; Li, Lanxin; Zhu, Weisheng; Wang, Luyao; Liu, Xingping; Bing, Wei; Zhang, Zhijun (Frontiers in Chemistry, 2022)
Photothermal treatment is an effective and precise bacterial disinfection method that can reduce the occurrence of bacterial drug resistance. However, most conventional photothermal treatment strategies have the problem that the photothermal response range does not match the infection area. Herein, a metal–organic framework (MOF) nanocomposite responding to the oxidation state of the bacterial infection microenvironment was constructed for near-infrared (NIR) photothermal bacterial inactivation. In this strategy, the MOF was used as a nanocarrier to load tetramethylbenzidine (TMB) and horseradish peroxidase (HPR). The high oxidation state of the bacterial infection microenvironment can trigger the enzyme-catalyzed reaction of the nanocomposite, thereby generating oxidation products with the NIR photothermal effect for bacterial disinfection. The synthesis and characterization of the nanocomposite, oxidation state (H2O2) response effect, photothermal properties, and antibacterial activities were systematically studied. This study provides a new idea for building a precision treatment system for bacterial infection.